Mineralização da matéria orgânica e lixiviação de solutos de águas residuárias de laticínios e abatedouro aplicadas em solos cultivados com capim-tifton 85 - Oliveira, Jacineumo Falcão de (2016)
The treatment and posterior adequate destination of wastewater is currently a relevant discussion in Brazil, given the scarcity of fresh water resources and the availability of wastewater either untreated or inefficiently treated. The wastewater from dairy industry (ARL) and abattoirs (ARA) are characterized by their high organic content, which represents potential harms to ecological systems. An accessible and efficient final destination for ARL and ARA would be deposition in soil. Soil presents a natural capacity of depuration, which along with plant works as a filter, where suspended particles and nutrients are retained and pathogens inactivated. Based on those facts, the aim of this study was to evaluate the mineralization of organic matter and lixiviation of solutes from ARL and ARA deposited in soil cultivated with 85 Tifton-grass. The experiment was composed of 27 PVC columns filled with red latosol. The treatments were randomized into four different nitrogen doses (150, 300, 450 e 600 kg ha -1 ) for each wastewater and one control treatment which received conventional fertilizing (150 kg ha -1 of N), three replications was considered for each treatments. The dosages of ARA, ARL and AQT0 were estimated according to the recommendation of 300 kg N ha -1 year -1 . The study included analysis of total, suspended and dissolved solids, pH, EC, NTK, PT, K, NO3 -, NO2 -, BOD, COD, Ca, Mg and Na present in the wastewaters considered in this study. Biological activity in the soil was estimated by means of basal soil respiration (BSR). The fertility of soil was estimated up to 20 cm of column height. At the end of experiment, the highest COD concentrations were equal to 46.9 and 38.3 mg L -1 for the highest doses of ARA and ARL, respectively, contrasting to 8.5 mg L -1 for the control. The concentrations of Nitrate in the percolates for all treatments were within the legislation limit, below 10 mg L -1 . After 116 days, it was observed a reduction of K, Ca+Mg and N-NO2 -. For treatments that received the maximum dosage of ARA and ARL, the productivities of 85 Tifton-grass were equal to 16.8 and 15.1 t ha -1 . The environment created by the interaction soil-plant in the columns leaded to a higher nutrient uptake by the 85 Tifton-grass at the second cut, especially for treatments that received the highest dosages of ARA, presenting 384 and 10.4 kg ha -1 of NTK and PT. A significant difference for BSR was not observed among treatments, however, the most expressive activities (704 e 251 μg kg -1 h -1 de C-CO2) were found for treatments that received the two and three times more N dose than the recommended.